Egocentric and exocentric teleoperation interface using real-time, 3D video projection - Ferland, François; Pomerleau, François; Le Dinh, Chon Tam; Michaud, François (2009 4th ACM/IEEE International Conference on Human-Robot Interaction (HRI), 2009)
The user interface is the central element of a telepresence robotic system and its visualization modalities greatly affect the operator's situation awareness, and thus its performance. Depending on the task at hand and the operator's preferences, going from ego- and exocentric viewpoints and improving the depth representation can provide better perspectives of the operation environment. Our system, which combines a 3D reconstruction of the environment using laser range finder readings with two video projection methods, allows the operator to easily switch from ego- to exocentric viewpoints. This paper presents the interface developed and demonstrates its capabilities by having 13 operators teleoperate a mobile robot in a navigation task.